Optical, Structural, Morphological Properties of Chromium (III) Oxide Nanostructure Synthesized Using Spray Pyrolysis Technique - Mohammed, Fatin Hameed; Mikhlif, Haitham M. (Iraqi Journal of Physics, 2021)
Nanostructure of chromium oxide (Cr2O3-NPs) with rhombohedral structure were successfully prepared by spray pyrolysis technique using Aqueous solution of Chromium (III) chloride CrCl3 as solution. The films were deposited on glass substrates heated to 450°C using X-ray diffraction (XRD) shows the nature of polycrystalline samples. The calculated lattice constant value for the grown Cr2O3 nanostructures is a = b = 4.959 Å & c = 13.594 Å and the average crystallize size (46.3-55.6) nm calculated from diﬀraction peaks, Spectral analysis revealed FTIR peak characteristic vibrations of Cr-O Extended and Two sharp peaks present at 630 and 578 cm-1 attributed to Cr-O “stretching modes”, are clear evidence of the presence of crystalline Cr2O3. The energy band gap (3.4 eV) for the chromium oxide nanostructures was measured using the UV-VIS-NIR Optical Spectrophotometer. It was found that by scanning electron microscopy (SEM) and image results, there is a large amount of nanostructure with an average crystal size of 46.3-55.6 nm, which indicates that our synthesis process is a successful method for preparing Cr2O3 nanoparticles.